Metastasis to an odontogenic cyst: case report and review of literature - Sadeghi, Shayan; Aubry, Claudya; Robin, Christian; Ghannoum, Julien (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Metastatic disease to the jawbone is relatively uncommon. However, its occurrence within a pre-existing odontogenic cyst or tumor is extremely rare. We present a case of a 61-year-old woman experiencing fatigue and nocturnal diaphoresis with an otherwise asymptomatic radiolucent lesion of the mandible. Radiographic features were suggestive of a benign odontogenic cyst. A biopsy revealed a metastatic nidus within the wall of a benign odontogenic cyst. Further investigations confirmed the presence of a primary pulmonary adenocarcinoma. Diagnosis of metastases to the orofacial region may be challenging because of their various clinical and radiographic features. Thorough histopathological analysis of any routine cystic tissue from the maxillofacial structures, even seemingly benign, is necessary to rule out more aggressive disease.